The Effect of Problem-Based Learning and Level Intelligence of Students’ Critical Thinking on Kalamm Science - Mardiah Astuti (Ta'dib: Jurnal Pendidikan Islam, 2016)
This research aim was to figure out the effect of  PBL and Level Intelligence of Student’s Critical Thinking. The subject matter in this research was Ilmu Kalam. This research was experimental design and used factorial design 2 x 2. The result of this research was: 1) There were differences in average critical thinking skills in the subject of Kalam  Science of the group given, the model PBM to Conventional Methods, 2)  there was evidence that the PBL model could improve critical thinking skills for students who had high intelligence, 3) The ability of students in critical thinking in that they had low intelligence by using higher PBM model with critical thinking skills of students with lower intelligence levels using conventional models, 4) the interaction effect between PBL and intelligence influential on the level of critical thinking skills of students.Tujuan penelitian ini adalah untuk mengetahui pengaruh PBL dan Tingkat Kecerdasan Berpikir Kritis Mahasiswa. Subyek dalam penelitian ini adalah Ilmu Kalam. Penelitian ini adalah desain eksperimental dan digunakan desain faktorial 2 x 2. Hasil penelitian ini adalah: 1) Ada perbedaan keterampilan berpikir kritis rata-rata di subjek Kalam Ilmu kelompok tertentu, model PBM ke Metode Konvensional, 2) ada bukti bahwa model PBL dapat meningkatkan kemampuan berpikir kritis bagi siswa yang memiliki kecerdasan yang tinggi, 3) kemampuan siswa dalam berpikir kritis dalam bahwa mereka memiliki kecerdasan yang rendah dengan menggunakan model PBM lebih tinggi dengan kemampuan berpikir kritis siswa dengan tingkat kecerdasan yang lebih rendah menggunakan model konvensional, 4) efek interaksi antara PBL dan kecerdasan berpengaruh pada tingkat kemampuan berpikir kritis siswa.